Nate the Great on the Owl Express - Sharmat, Marjorie Weinman (Dell Yearling, 2004)
While traveling on the train to San Francisco with his cousin Olivia's owl, Nate the Great and his dog Sludge must use all of their detective skills when the owl suddenly disappears.